COMPETITIVE ADVANTAGE THROUGH MARKET ORIENTATION, CREATIVITY AND PRODUCT INNOVATION - Rahmat Budi Hidayat,; Endang Silaningsih,; Yulianingsih, (Jurnal Visionida, 2024)
This research focuses on the use of market orientation, creativity, and product innovation as key strategies. This research uses quantitative methods and collects primary data through questionnaires and direct interviews with MSME owners. The sample size consisted of 100 respondents selected using proportional stratified random sampling technique with purposive sampling method. The data were analysed using descriptive verification analysis, validity and reliability tests, multiple linear tests and classical assumption tests. The results showed that creativity, innovation, and market orientation have a positive and significant effect on competitive advantage, both individually and jointly.